Pengaruh Kepemimpinan Kepala Sekolah dan Sarana Prasarana terhadap Kinerja Guru SMP di Kecamatan Cibinong Bogor - Fuji Ria Tambunan; Imam Tholkhah; Mohamad Jaenudin (Jurnal Dirosah Islamiyah, 2020)
The background of this research is the teacher as a component that greatly influences the educational process and the main factors that determine the quality of education. The teacher is the spearhead that is directly related to students as the subject and object of learning in the teaching and learning process. The availability of a good education curriculum, complete educational facilities and infrastructure, but if not balanced with the ability of teachers who are able to implement it, then everything will be less meaningful and not support the achievement of educational goals. The study was conducted at a junior high school located in the District of Cibinong, Bogor Regency. The purpose of this study was to determine the effect of Principal Leadership and Infrastructure Facilities on the Performance of Junior High School Teachers in Cibinong District, Bogor Regency. This research is a quantitative study using a survey approach to obtain an overview and correlation of research variables, namely Principal Leadership (Variable X1), Infrastructure Facilities (variable X2) and Teacher Performance (variable Y) of SMP in Cibinong District, Bogor. Data collection techniques used were observation, documentation study, questionnaires. Data analysis techniques through three stages, namely descriptive analysis, quantitative analysis and research hypothesis testing. The results showed that (1) the Principal's Leadership influenced significantly and rather high and the direction of a positive relationship to the Performance of Junior High School Teachers in Bogor Regency. (2) The Infrastructure Facility influence significantly and has a rather high and direction of a positive relationship to the Performance of Junior High School Teachers in Bogor Regency. (3) The joint effect of School Principals and Infrastructure Leadership on the Performance of Junior High School Teachers in Bogor Regency is high